Inflammatory Pseudotumor of the Ulnar Nerve Mimicking a Malignant Peripheral Nerve Sheath Tumor: A Radiologic Puzzle - Abelkis, Eimantas; van Langevelde, Kirsten; Doeleman, Thom; Groen, Justus; Navas Cañete, Ana (Seminars in Musculoskeletal Radiology, 2024)
Inflammatory pseudotumor (IPT) of a peripheral nerve is a rare non-neoplastic tumefactive inflammatory condition, often mimicking malignancy. The etiology of this condition is still unknown. Clinically and radiologically, the lesion can mimic a malignant tumor. This case report represents, as far as we know, the first publication describing the ultrasonography findings and the results of advanced dynamic contrast-enhanced magnetic resonance imaging (MRI) and diffusion-weighted MRI of IPT in a peripheral nerve. Suspicion of this entity on imaging can speed up the definitive diagnosis and potentially avoid overly radical treatment.
Keywords: inflammatory pseudotumor of a peripheral nerve; peripheral nerve pseudotumor; inflammatory pseudotumor magnetic resonance imaging; inflammatory pseudotumor ultrasonography